CEO CHARACTERISTICS AND FINANCIAL REPORTING QUALITY IN LISTED CONSUMER GOODS COMPANIES IN NIGERIA - Nkiru Philomena Okika; Oyeneye Temitope Esther; Adedeji Daniel Gbadebo (Gusau Journal of Accounting and Finance)
This study investigates the connection between the CEO characteristics and the quality of financial reporting in Nigerian consumer goods companies. Data used was from the annual report of 10 consumer goods firms listed in the Nigeria Stock Exchange from 2013 to 2022. Using Ordinary least square regression, the research revealed that CEO gender and tenure have a positive and substantial effect on financial reporting quality. CEO financial expertise was found to be insignificant. The study concluded that long-tenure CEOs and female CEOs contribute to better financial reporting quality in the consumer goods industry. The study recommends among others that the board of directors of consumer goods firms in Nigeria should encourage gender diversity at the executive level through policies and initiatives that promote equal opportunities for women.